2021
DOI: 10.1177/10711007211050876
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Aseptic Revision of Operatively Treated Ankle Fractures

Abstract: Background: Early revision rates within 12 months after ankle fracture open reduction internal fixation (AF-ORIF) are fairly low; however, they remain relevant given the volume of ankle fractures occurring annually. Understanding these rates is complex because reoperation due to technical or mechanical complications is typically reported alongside soft tissue–related problems such as symptomatic hardware, wound dehiscence, or infection. There are limited data identifying risk factors specifically for revision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Pilskog et al 20 retrospectively analysed 478 cases of ankle fracture in New Jersey from 2003 to 2010. it was found that 95.8% of the patients had good wound healing, 2.9% had mild complications and 1.3% had serious complications. In this study, we calculated that the incidence of wound complications was 19.0%, which was consistent with the incidence of 1.4% to 18.8% in previous studies 12,21 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Pilskog et al 20 retrospectively analysed 478 cases of ankle fracture in New Jersey from 2003 to 2010. it was found that 95.8% of the patients had good wound healing, 2.9% had mild complications and 1.3% had serious complications. In this study, we calculated that the incidence of wound complications was 19.0%, which was consistent with the incidence of 1.4% to 18.8% in previous studies 12,21 …”
Section: Discussionsupporting
confidence: 89%
“…Some scholars believe that advanced age is a risk factor for wound complications, 22 diabetes is a recognised risk factor for infection 23 . Previous studies have also shown that injury mechanism, open fracture and wound classification are also risk factors for wound complications after ankle fracture 21,24,25 . In this study, we identified nine independent risk factors associated with an increased risk of postoperative wound complications in patients with ankle fracture.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Stupay et al 31 performed a retrospective cohort study to identify risk factors for aseptic revision of operatively treated ankle fractures. Using multivariable logistic regression modeling, the authors reported that falls in the early postoperative period, movement-altering disorders, a nonanatomic mortise (medial clear space was greater than superior clear space) on initial postoperative imaging, more severe initial fracture displacement, substance abuse, and polytrauma are independent risk factors for aseptic revision after ankle ORIF.…”
Section: Traumamentioning
confidence: 99%